2009
DOI: 10.1080/10803548.2009.11076822
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychosocial Work Factors, Work Stress and Computer-Related Musculoskeletal Discomforts Among Computer Users in Malaysia

Abstract: Increasing numbers of workers use computer for work. So, especially among office workers, there is a high risk of musculoskeletal discomforts. This study examined the associations among 3 factors, psychosocial work factors, work stress and musculoskeletal discomforts. These associations were examined via a questionnaire survey on 30 office workers (at a university in Malaysia), whose jobs required an extensive use of computers. The questionnaire was distributed and collected daily for 20 days. While the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 27 publications
1
29
0
7
Order By: Relevance
“…Em virtude disso, as alterações posturais, especialmente nas faixas etárias mais jovens, têm sido objeto de vários estudos, devido às posturas incorretas e sedentarismo característicos da vida moderna, sendo, muitas vezes, observados em pessoas que ficam sentadas durante longos períodos de tempo, o que repercute em dores lombares, em decorrência do aumento da compressão nos discos intervertebrais e dores cervicais pela flexão cervical excessiva (ZAKERIAN; SUBRAMANIAM, 2009;VILELAS;LOPES, 2012;CADÓ et al, 2013).…”
Section: Discussionunclassified
“…Em virtude disso, as alterações posturais, especialmente nas faixas etárias mais jovens, têm sido objeto de vários estudos, devido às posturas incorretas e sedentarismo característicos da vida moderna, sendo, muitas vezes, observados em pessoas que ficam sentadas durante longos períodos de tempo, o que repercute em dores lombares, em decorrência do aumento da compressão nos discos intervertebrais e dores cervicais pela flexão cervical excessiva (ZAKERIAN; SUBRAMANIAM, 2009;VILELAS;LOPES, 2012;CADÓ et al, 2013).…”
Section: Discussionunclassified
“…Several studies which were conducted among adults working in offices in Malaysia concluded that computer use could be a risk factor in developing musculoskeletal problems (Zakerian and Subramaniam, 2009;Rahman and Atiya, 2009;Sen and Richardson, 2007). However, there is little information on the prevalence of musculoskeletal complaints among college students in Malaysia using computers.…”
Section: Discussionmentioning
confidence: 99%
“…A large study of Taiwanese workers found job content, lack of career prospects, and job organizational problems, were important risk factors for women with self-reported MSP working in public administration roles [18]. Zakerian and Subramaniam [19] found psychosocial work factors associated with work stress and MSDs in a Malaysian office based population included job demands, lack of job control, social support and negative social interactions. The authors had previously reported that being female, having lower levels of work-life balance and poorer mental health levels, and being exposed to high physical demands were predictors of MSP [3].…”
Section: Introductionmentioning
confidence: 99%